(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article analyzes the linguistic and cultural features of jewelry used in Uzbek folk tales in the linguistic consciousness of the Uzbek people. The relevance of the article is due to the fact that it is dedicated to the national-mental characteristics of earrings, rings and bracelets in the world and Uzbek people’s minds in the linguistic landscape of the world.